Topology optimization of cast parts considering parting surface position. (November 2020) - Wang, Chao; Xu, Bin; Meng, Qingxuan; Rong, Jianhua; Zhao, Yonghui
Highlights: Independent of the parting surface in the design domain. Provide optimal castable design and parting surface position. Capable of considering the user-specified parting surface position. The method is simple and easy to implement. Numerical examples illustrate the effectiveness. Abstract: Topology optimization of cast parts involving parting surface position is one of the main challenges in engineering design. This work presents a study on topology optimization of cast parts considering various cases of parting surface position. Two casting constraint models for different parting surface position requirements are developed and evaluated. One is a variable parting surface model to achieve the optimal castable design and parting surface position. Another is a virtual parting surface model for generating the required castable design with the user-specified parting surface position. The simple but efficient finite element method-based optimization algorithm is employed to simplify the optimization process. And the density filter-based threshold projection technique is utilized to enhance the 0–1 solution. Besides, the effects of the parting surface position, parting direction, loading path, and material volume on the resulting castable designs are investigated. Numerical examples are provided and compared with the existing methods to illustrate the effectiveness of the proposed method. This method does not depend on the fixed parting surface in the design domain as usual. Therefore, it can be used to produce high-performance castable designs with reasonable material layout and smooth boundaries.